2012
DOI: 10.1097/psy.0b013e318244c604
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury (Concussion), Posttraumatic Stress Disorder, and Depression in U.S. Soldiers Involved in Combat Deployments

Abstract: These data indicate that current screening tools for mTBI being used by the Department of Defense/Veteran's Affairs do not optimally distinguish persistent postdeployment symptoms attributed to mTBI from other causes such as PTSD and depression. Accumulating evidence strongly supports the need for multidisciplinary collaborative care models of treatment in primary care to collectively address the full spectrum of postwar physical and neurocognitive health concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 38 publications
2
122
0
Order By: Relevance
“…Even more optimal than referral is integrated assessment and treatment with open communication among multiple disciplines when providing care to veterans with PTSD, MDD, and a history of TBI. These associations support the interdisciplinary treatment model and previous recommendations to make functional improvement a greater priority than treatment of individual symptoms (Wilk et al, 2012).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Even more optimal than referral is integrated assessment and treatment with open communication among multiple disciplines when providing care to veterans with PTSD, MDD, and a history of TBI. These associations support the interdisciplinary treatment model and previous recommendations to make functional improvement a greater priority than treatment of individual symptoms (Wilk et al, 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Because of symptom overlap, the interaction among PTSD, MDD, and a history of TBI is complicated and not fully understood, making overall functional improvement perhaps a greater priority than specialty treatment of individual symptoms (Wilk, Herrell, Wynn, Riviere, & Hoge, 2012). Providing the most comprehensive evidencebased care in the treatment of these combined conditions requires collaboration among disciplines, which preliminary research has suggested improves outcomes for people with chronic conditions (Hand, Letts, & von Zweck, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a high level of co-occurrence of TBI and PTSD in this population. Many observational studies from both military and civilian settings (Hoge et al, 2008;Schneiderman et al, 2008) have firmly established an association between mTBI and PTSD (Hoge et al, 2008;Schneiderman et al, 2008;Carlson et al, 2011;Hart et al, 2014;Stein and McAllister, 2009;Tanev et al, 2014;Wilk et al, 2012;Wisco et al, 2014;Yurgil et al, 2014). These observations signal not only a need for effective interventions for PTSD and mTBI occurring individually, but for interventions that have the potential to address both conditions at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Mild brain concussive injury can cause cognitive and emotional dysfunction and increase the risk for the development of anxiety disorders, including PTSD (Carlson et al, 2011, Wilk et al, 2012. The N-methyl-D-aspartate (NMDA) glutamate receptors in the amygdala appear to regulate fear and anxiety.…”
Section: Glutamate Release In Mild Tbimentioning
confidence: 99%